The Forum Politics in Early Roman Empire (British Journal of Multidisciplinary and Advanced Studies, 2025)
This article investigates the political dynamics of forum space in the early Roman Empire by employing a power-space analytical framework. Focusing on the transition from the Republic to the Principate, it examines how public architecture, legislative venues, and triumphal rituals were spatially reorganized to support imperial consolidation. By analyzing Caesar and Augustus’s manipulation of spatial structures—from the relocation of rostra and construction of imperial fora to the invention of triumphal honors—this paper reveals a complex grammar of visibility and authority. The forum emerged not merely as a civic stage, but as a domain of power contestation, where rituals and spatial design encoded strategies of inclusion, exclusion, and legitimation.